Field notes contributed by James L. Hansen, spring 1987 - Hansen, James L.et al (1987)
List of birds and locations contributed by James L. Hansen with observers Curt Nelson, Ted LaGrange, Lowell Washburn and others. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of spring 1987. Epson - sheet feed